2022
DOI: 10.4274/tjo.galenos.2021.33723
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Nanophthalmos-Related Uveal Effusion with Two- vs. Four-Quadrant Partial-Thickness Sclerectomy and Sclerotomy Surgery

Abstract: Objectives: To report visual and anatomical outcomes following two- or four-quadrant partial-thickness sclerectomy and sclerotomy surgery to treat nanophthalmos (NO)-related uveal effusion (UE). Materials and Methods: Consecutive patients with NO-related UE were treated with four-quadrant or two-quadrant (for those with associated glaucoma) partial-thickness sclerectomy and sclerotomy surgery. Axial length, extent of UE, preoperative, postoperative, and final best corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Special anatomic features of nanophthalmos. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] zonular dialysis occurred after a cotton applicator was applied to the injection site in an effort to control the reflux of hyaluronic acid or air. The lens dislocated into the vitreous cavity in Cases 4 and 5 after the eye was reinflated with a balanced salt solution injected through a limbal incision.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Special anatomic features of nanophthalmos. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] zonular dialysis occurred after a cotton applicator was applied to the injection site in an effort to control the reflux of hyaluronic acid or air. The lens dislocated into the vitreous cavity in Cases 4 and 5 after the eye was reinflated with a balanced salt solution injected through a limbal incision.…”
Section: Resultsmentioning
confidence: 99%
“…These eyes have very anterior insertion of the retina, a large lens, short zonules, a shallow anterior chamber (AC) (with a propensity for angle closure), and a noticeably thickened sclera and choroid (Figure 1). [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Vitrectomy is dangerous because it can result in peripheral holes (anterior retinal insertion), 12 which can cause an exudative RD to become more complex and require silicone oil tamponade or multiple surgical procedures. 12,13 In this case series, we describe the anatomic and visual results of surgical procedures for serous RD with retina-lens touch in eyes with nanophthalmos.…”
Section: Introductionmentioning
confidence: 99%
“…The study included eight nanophthalmic eyes with uveal effusion and reported resolution of the effusion in all eyes with an average of 13.9 days, however, the effusion recurred in one eye with a retinal vasoproliferative tumor [56]. In a recent study, Ozdek and colleagues found that in nanophtahlmic-related effusion, performing four-quadrants sclerectectomies was more effective than two-quadrants sclerectomies [57]. While the majority of the literature is focused on partial thickness sclerectomy, full thickness scleral cuts have also been performed [58].…”
Section: Intra- and Postoperative Complicationsmentioning
confidence: 99%